What rural ecological governance goals do local residents prefer? Evidence from Hainan, China - Han Liu; Dan Qiao; Tao Xu (Sustainable Futures)
Rural ecosystems restoration requires the joint participation of rural residents and government in governance. This study aims to analyze whether rural ecological governance goals are consistent with rural residents' preferences and how they affect rural residents' utility levels, which are key to rural residents' ecological governance participation behavior. Using survey data from 653 rural residents in Hainan Island, China, this paper applies a choice experiment method and a random parameter logit model to identify differences in rural residents' preferences for different rural ecological governance policy goals and their governance participation behaviors. The results show that increasing the coverage rate of sewage treatment facilities, reducing fertilizer and pesticide application, and increasing rural biodiversity can significantly enhance rural residents' ecological governance participation utility, thereby promoting their choice of ecological governance options. Rural residents' participation behavior in rural ecological governance is also influenced by individual and household characteristics such as ethnicity, labor size, net farm income, ICT usage, and ecological knowledge level. Based on these findings, policymakers should strengthen communication of governance policies and objectives, respect rural residents' policy goal preferences, prioritize the implementation of rural ecological governance models that increase the coverage of wastewater treatment facilities, reduce fertilizer and pesticide application, and increase rural biodiversity, and rely on ICT devices to popularize ecological knowledge among rural residents.